EKSISTENSI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SEKOLAH DASAR DALAM KONTEKS PENDIDIKAN POLITIK UNTUK MEMBANGUN KEMELEKWACANAAN POLITIK (POLITICAL LITERACY) WARGA NEGARA - Denny Soestisna (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
The realization of the good citizens (good citizen) is a citizen of political savvy, political awareness, and participation in political life is the ultimate goal of education politik.Dalam this political education in Indonesia is directed to improve and develop the awareness of national and state corresponding with the philosophy of Pancasila and the 1945 Constitution granted Indonesian political education in primary schools is through the subject matter of Pancasila and Citizenship Education (PPKn). The political education aims to gain knowledge of the politics of every citizen to go through the learning process simultaneously and continuously. A citizen can be directed to be sensitive to social and political problems that occur in the vicinity, until at last they can appear as a solver of these problems. In Decission making this process was not only necessary knowledge (civic knowledge), but needed also their virtue citizens (beliefs: civic virtues) and participation skills (skills: civic participation). This is the role of Citizenship at the elementary level. Keywords : Political Literacy, Political Education, Primary School